The Effectiveness of the Family Program (PKH) Management for Poverty Reduction in Karang Tempel Village, East Semarang District, Semarang City, Central Java, Indonesia - Ginting, Rosalina; Noor, Munawar; Widodo, Suwarno; Istyaningsih, Rusmiyatun (Advances in Social Sciences Research Journal, 2022)
The problem study of this research was how effective the Family Hope Program management for Poverty Reduction. The purpose of the study was to describe and analyze the effectiveness and the driving/inhibiting factors for the program management. The theoretical basis of this research is that public policy is a policy made by the government as a policy maker to achieve certain goals in society which in its preparation go through various stages. Policy implementation was considered as a process of moving toward a policy objective by means of administrative and political steps. The implementation of this policy is not only concerned with the mechanism of elaborating political decisions into routine procedures through bureaucratic channels, but more than that, it concerns the issue of conflict, the decision of who gets what from a policy. Effectiveness was a criterion for selecting various alternatives to be used as recommendations based on the consideration of whether the recommended alternative provides maximum results (effect), regardless of efficiency considerations. Effectiveness emphasized more on aspects of the goals of an organization, so if an organization has succeeded in achieving the goals that have been set, it has achieved effectiveness. This research type was the field research which aimed to study intensively about the background of the current situation, and the interactions of the social environment, individuals, groups, institutions, or communities. The results of this study indicated that the PKH program has not been fully effective due to various program constraints. Recommendation: this program requires a simple and easy to implement program mechanism model